The rise of judicial diplomacy in the UK: aims and challenges. (March 2020) - Davies, Gregory
Abstract: This paper examines the aims and challenges of 'judicial diplomacy' in the form of bilateral meetings between UK and supranational judges. Drawing from in-depth interviews, extra-judicial writings and other documentary sources, it argues that judicial diplomacy has become an important feature of the work of senior judges in the UK, allowing them to pursue jurisprudential and strategic aims. In jurisprudential terms, the judges have sought to improve the quality of judicial decision-making at the domestic and supranational levels. Strategically, they have striven to maintain robust inter-institutional relations and maximise their influence at the supranational level. The pursuit of these aims has taken on renewed significance in the context of Brexit but may raise questions for the protection of judicial independence and impartiality. The judiciaries should therefore consider steps to improve the visibility of these interactions and their value.